Konstruksi Sosial Penerima Program Bantuan Stimulan Perumahan Swadaya (BSPS) Sebagai Identitas Sosial: Studi Kasus Desa Pendem, Kecamatan Mojogedang, Kabupaten Karanganyar - Armeita Khalawati (Universitas Sebelas Maret (UNS), 2025)
Bantuan Stimulan Perumahan Swadaya (BSPS) aims to accelerate the resolution of uninhabitable housing issues under the Directorate General (Ditjen) of Housing, Ministry of Public Works and Public Housing. This objective is carried out through a scheme that enhances self-sufficiency among low-income communities to improve the quality of habitable housing. This study aims to understand how social construction is formed regarding beneficiaries, how the social identity of beneficiaries develops, and the factors influencing the social construction of BSPS recipients in Pendem Village, Mojogedang District, Karanganyar Regency. This research employs Peter L. Berger’s Social Construction Theory to comprehensively explore the data. A qualitative method with a case study approach was used to highlight processes and meanings by deeply understanding, exploring, and describing data obtained from informants. The focus of this case study research lies in contemporary phenomena within real-life contexts. Data sources consist of primary data collected through interviews, observations, and documentation involving the local community surrounding BSPS beneficiaries, as well as secondary sources from relevant literature. The findings indicate that the BSPS program fosters diverse forms of social construction, including social participation, changes in stigma, and a more positive social recognition of beneficiaries. The social identity of recipients emerges through greater acknowledgment, self-sufficiency, and participation in community cooperation. The key factors influencing social construction toward beneficiaries include economic, social, political, and religious aspects.